2022
DOI: 10.3390/su14073910
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Architectural Thermal Envelope Parameters in Modern Single-Family House Typologies in Southeastern Spain to Improve Energy Efficiency in a Dry Mediterranean Climate

Abstract: The increasing regulatory requirements for energy efficiency in Europe imply a significant increase in insulation and solar control of buildings, especially in hot and semi-arid climates with high annual insolation such as the Spanish Mediterranean southeast. The consequences in architectural design to optimize compliance with the new technical and regulatory requirements of nearly zero-energy buildings are high. This paper analyzes the energy performance of a modern single-family house on the Spanish Mediterr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 46 publications
0
6
0
1
Order By: Relevance
“…The thermal insulation layer could separate the indoor conditioned air from the high outdoor temperature, and reduce cooling energy dissipation. Insulating the building envelope is usually a key measure that is required in deep energy retrofitting, which aims to achieve very low energy consumption, as it also assists in creating a steady indoor environment that allows other systems to work at a more desired efficiency [20]. However, within a climate warming scenario, it is important to include future climate possibilities in decisions on the insulation material's thickness, for the sake of avoiding overheating in the future [21,22].…”
Section: Energy Conservation-related Passive Measuresmentioning
confidence: 99%
“…The thermal insulation layer could separate the indoor conditioned air from the high outdoor temperature, and reduce cooling energy dissipation. Insulating the building envelope is usually a key measure that is required in deep energy retrofitting, which aims to achieve very low energy consumption, as it also assists in creating a steady indoor environment that allows other systems to work at a more desired efficiency [20]. However, within a climate warming scenario, it is important to include future climate possibilities in decisions on the insulation material's thickness, for the sake of avoiding overheating in the future [21,22].…”
Section: Energy Conservation-related Passive Measuresmentioning
confidence: 99%
“…Previous research has demonstrated the high greenhouse effect generated by glazed surfaces in the BShs climate [22] and the beneficial effect of natural ventilation in dissipating excess heat from the indoor environment [23][24][25][26][27]. Some case studies consider modern single-family houses with large windows, or public buildings with large semi-transparent roofs, such as sports buildings or heated public swimming pools [28].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated the effect of high solar radiation on the thermal performance of buildings with considerable glazing in the BShs climate [26,27]. High solar radiation increases the radiant temperature of interior façade surfaces, greenhouse effect inside buildings, and operating temperature.…”
Section: Introductionmentioning
confidence: 99%